Responding to a corruption crisis through disclosure and remedial action: the case of Petrobras - Whitehead, Martin; Belghitar, Yacine (Elsevier, 2022)
This case study adopts a positivist perspective to examine how Petroleo Brasileiro S.A (“Petrobras”), a high-profile company in its native Brazil with multiple listings including in Brazil and the US, responded to a major corruption scandal arising in 2014. We consider Petrobras's response both in terms of its visible activities – i.e. in relation to anti-corruption and compliance (“ACC”) disclosures in its annual report (AR) and sustainability report (SR), as well as actioned remedial policies that constitute the crisis plan – and how the company went about interacting with stakeholders during and after the immediate crisis period. We conducted a content analysis of ACC disclosures and assessed Petrobras's remedial activities in the eight-year period 2010–2017 as disclosed in its ARs, SRs and press releases. We find firstly that, consistent with legitimacy theory, Petrobras responded by voluntarily and substantially increasing its relevant disclosures so as to regain legitimacy, a finding which mirrors those found elsewhere following corruption and environmental crises. Secondly, the unique corporate governance situation at Petrobras combined with the fact that leadership was allegedly implicated in the scandal, led the post-crisis management team to undertake a series of remedial actions that prioritised the need to take and maintain executive control and independence from the government, whilst at the same time carefully managing the relationship with this influential stakeholder: - actions which argue strongly in favour of stakeholder-agency theory and multiple agency theory interpretations of the nature of stakeholder interactions that transpired during the crisis period of disequilibrium, and which precluded the type of stakeholder dialogue seen in some previous environmental crisis situations. Finally, we show that Petrobras's crisis management response actions align well with models of trust repair and legitimacy management, and suggest the company considered it had successfully regained legitimacy by 2017.
Keywords: Anti-corruption; Compliance; Legitimacy; Multiple agency theory; Stakeholder-agency theory; Trust repair; Voluntary disclosure